Smaller but not Secondary: Evidence of Rodents in Archaeological Context in India. (29th June 2017) - Sathe, Vijay
The small site archaeology has a remarkable potential to contribute on many greater issues in archaeological studies. Similarly, micro dimensional data of any category should prove to be of great importance if studied judiciously. The present paper intends to point out this very fact with a special reference to skeletal remains of micromammals in the category of rodents as a special case. This topic has been specifically undertaken because it is largely observed that such skeletal material tends to be overlooked and sometimes even totally discarded as of no archaeological significance. Rats and mice (muroids, Order: Rodentia) are one of the world's ubiquitous small rodents whose antiquity in India goes back to the Tertiary period. Its skeletal remains have been reported from several archaeological sites in India with temporal range of about 20 ka. Rodents have the potential to provide palaeoenvironmental information not attainable from other animal groups. The fact is well appreciated in palaeoentology but unfortunately remains to be confronted in archaeological context so far. The present paper ventures to ponder upon the possibilities of palaeoenvironmental interpretations of rodent fauna in archaeological record. A sizable assemblage of microvertebrates excavated from an Early Historic site of Kopia, Dist. Sant Kabirnagar (Uttar Pradesh state of India) offers a case study of microfaunal interpretations. Evidence of muroid's contribution to the diet of ancient human population is discussed with reference to several existing hunting gathering communities practicing small game and the Musehars, aborigines living in the interiors of Gangetic plains. It provides a ready database for the dietary inferences with regard to the rodent fauna that are interpreted from archaeological perspective. The paper demonstrates multifold implications of evidence of rats and mice in archaeololgical record that have significant bearing on the ecology, subsistence and behavioural archaeology.